If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 360 = 145 + 66 + 63 + x + 57 Reorder the terms: 360 = 145 + 66 + 63 + 57 + x Combine like terms: 145 + 66 = 211 360 = 211 + 63 + 57 + x Combine like terms: 211 + 63 = 274 360 = 274 + 57 + x Combine like terms: 274 + 57 = 331 360 = 331 + x Solving 360 = 331 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 360 + -1x = 331 + x + -1x Combine like terms: x + -1x = 0 360 + -1x = 331 + 0 360 + -1x = 331 Add '-360' to each side of the equation. 360 + -360 + -1x = 331 + -360 Combine like terms: 360 + -360 = 0 0 + -1x = 331 + -360 -1x = 331 + -360 Combine like terms: 331 + -360 = -29 -1x = -29 Divide each side by '-1'. x = 29 Simplifying x = 29
| 3g-6=12 | | 3g-6=-12 | | 9x^2-72x-16y^2-3y-16=0 | | 15-z=1 | | 360=100+66+45+12x-7 | | Z+3x-2+z-5x+7= | | 4x/7-x | | 12(x+8)=8*30 | | sqrt(x+6-5)=0 | | y=1/4x^2-9 | | 585+.13x= | | 1/2.9.h=94.5 | | 2+13=30 | | ln(8x^2-5x+1)=0 | | 3x-9=3x-3 | | -196=7x+7(5x+14) | | 525+.21x= | | 1-(1-6m/7) | | (y^2x)*(y^2)-4(y^3)=0 | | 5x-5(4x+31)=-290 | | 43+x=253 | | 3y*3= | | 2(6x-4)=4(5x+3) | | 16y^2-3y+2.25=0 | | log(25x)-log(x-1)=2 | | 360=128+128+52+6x-8 | | -41+4x=79 | | log(b)=0.31 | | 5s+2r+6-3r-2= | | 2(4x-1)=3(3x-5) | | 8(-10x+21)=728 | | -32=0 |